DEVELOPMENT OF AN E-MODULE CONTAINING ICARE (INSTRUCTION, CONNECTION, APPLICATION, REFLECTION, AND EXTENSION) IN THE TOPIC OF TRIANGLES FOR EIGHTH GRADE - Nurfaojah, Ojah Siti; Wahyuni, Sulis; Dewi, Irmawati Liliana Kusuma; Nopriana, Tri (Jurnal Pendidikan Matematika dan IPA, 2025)
The development of mathematics e-modules to support learning has been widely conducted; however, e-modules designed with ICARE components on the topic of triangles remain limited. This study aims to develop mathematics teaching materials in the form of an ICARE-based e-module for the topic of triangles for eighth-grade students. The research type used is development or Research and Development (R&D) employing the ADDIE development model. However, the implementation was limited to three stages: Analysis, Design, and Development. The subjects of this study were two mathematics teachers. The e-module was validated by content experts and design experts. Instruments used to collect data included interviews, validation questionnaires, and educator response questionnaires. The analysis stage results indicate that students require alternative digital teaching materials to support learning. In the design stage, an ICARE-approach mathematics e-module on triangles was developed to facilitate student understanding. The development stage included validation tests by content and design experts, yielding highly valid results. The e-module"™s content validity reached 91.35%, categorized as very valid, while its design validity reached 87.21%, also categorized as very valid. Additionally, a practicality test by educators yielded a result of 66.80%, categorized as sufficiently practical. Thus, this e-module is expected to serve as an alternative digital teaching material that effectively supports the mathematics learning process and acts as a self-learning medium for students, thereby increasing student motivation. It is also expected that future research will consider this e-module as an additional learning resource for teachers that can support differentiated instruction.